Parent Involvement in Child Education as a Correlate of Academic Performance: Analyzing Denominational Secondary Schools in Uganda - Sekiwu, Denis; Kaggwa, Victoria Tamale (Advances in Social Sciences Research Journal, 2019)
The study examined how parent involvement in child education influences students’ academic performance in secondary schools in Tororo district, Uganda, with parents’ socio-economic status as the control variable. The comparative research design was employed with a sample of 360 students from eight denominational schools. The Parent Involvement Guide (PIG) was used to collect data and quantitative data analysis indicated that parent involvement in child education positively influences students’ academic performance. There are differences in students’ academic performance among different denominational schools with Moslem schools performing least with low parent involvement in child education, and Catholic schools performing highest with high parent involvement in child education. Parent involvement in child education is higher at home than in the school. Thus, parents are encouraged to get involved in child education and there is need to encourage schools to focus their values-orientations on increasing students’ academic performance.